IMPOSSIBLE TO GET IELTS 5 OR ABOVE IN 3 MONTHS, BUT… - Madumarov M.M (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The thesis shows the impact of innovative technologies and easy methods of language learning as well as information about the role of innovative technologies in language learning.